Construction of the 2024 Presidential Candidate Campaign on the Mata Najwa YouTube Channel - Basarah, Finy Fitrya (MediaKom : Jurnal Ilmiah Komunikasi, 2024)
The General Election ended on February 14, 2024, the Indonesian public is waiting for an official announcement from the General Election Commission (Komisi Pemilihan Umum). Previously, during the campaign period, after the campaign and waiting for the decision, news about the election, especially the Presidential Campaign, was widely discussed in the media, including YouTube.Najwa Shihab's YouTube channel, broadcast “Jejak Kampanye Capres 2024” (Traces of the 2024 Presidential Candidate Campaign) before the election was held. The content is divided into "Intro", "Jejak Kampanye Anis Baswedan", "Jejak Kampanye Prabowo Subianto", "Jejak Kampanye Ganjar Pranowo", and "Closing".By using Entman’s framing analysis, the research results that Mata Najwa is trying to remain neutral, provides a political identity or image for each presidential candidate that can influence people in choosing. But, even though she looks neutral, Mata Najwa positions the 2nd presidential candidate, Prabowo, as looking more relaxed and better prepared for the Presidential Election this time. Prabowo's style and strategy might be still old, but it turns out he is able to give his own image with the "contemporary" term, and is not owned by other Presidential Candidates. This image seems to have just appeared, not part of a previous strategic plan.